Amber in the Poem "De Rana et Lacerta, Succino Prussiaco Insitis" (About a Frog and a Lizard Embedded in Prussian Amber) by Daniel Hermann (1543—1601), a Humanist from Riga - Kreigere-Liepiņa, Laura (Kaliningrad Regional Amber Museum, 2016)
Poet Daniel Hermann (1543–1601), a 16th-century humanist and diplomat from Prussia, authored the poem "About a Frog and a Lizard Embedded in Prussian Amber," which was published in Riga in 1600. This poem is among the earliest works in Riga focused on natural sciences. The central "characters" in the poem are a frog and a lizard trapped in Prussian amber. The article revises the views of 16th century scientists on the origin of amber and the formation of amber inclusions. In the lines of the poem, Daniel Hermann allows the reader to get to know the use of amber in the medicine of the early modern period. Due to his excellent Latin language skills and extensive knowledge, the literary works of Daniel Hermann can be considered an important contribution to the literary heritage of Riga's humanists.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Research Subject Categories::NATURAL SCIENCES; humanism; Neo-Latin poetry; natural philosophy; amber inclusions; amber in medicine